Contextual Effect of Wealth on Independence: An Examination through Regional Differences in China - Takemura, Kosuke; Hamamura, Takeshi; Guan, Yanjun; Suzuki, Satoko (Frontiers in Psychology, 2016)
The current study disentangled two different effects of wealth on psychological tendency toward independence: one is an effect exerted at the individual level (i.e., effect of being rich) and the other is a contextual effect (i.e., effect of being surrounded by rich individuals). Past research has found a stronger tendency toward independence among people in economically developed societies. This association has often been explained as a result of a greater amount of choices, and thus more opportunities to express individuality that wealth affords individuals. In addition to this individual-level process, theories in cultural psychology imply that the wealth-independence link also reflects social processes––living in a rich society, regardless of one’s own wealth, promotes independence (contextual effect of wealth on independence). Through a large-scale survey in China, using multilevel analyses we found that wealth had both the individual-level effect and contextual effect on independence as well as related psychological tendencies (influence orientation and generalized trust), suggesting that individuals are more likely to be independent with greater personal wealth and when surrounded by wealthy others. Possible processes through which independence is promoted by living in a wealthy area are discussed.